O ciclo vital da família rondonopolitana - Rodrigues, Anaclara Miranda (2015)
This work proposes to bring awareness about the family s life cycle to the population that lives in the region of Rondonopolis, Mato Grosso. Considering that Brazil is a a continent-sized territory with diverse cultural influences, we must coin the term Brazilian Families . Based on a systemic theory, we established the Family as a system, in constant motion between influencing and being influenced by the context in which it is inserted. Therefore, this is a descriptive research, which the objective of characterizing the life cycle of the Rondopolitan family, describing its structure, dynamics and values. The population in the study consisted of 189 middle class families from the aforementioned region. After data collection, these were plugged into a spreadsheet application, using as criterium for analysis the frequency of received answers. The research showed a strong feature of the contemporay Rondopolitan Family that, despite its contemporariety, is still attached to traditional values. We noticed that the Rondopolitan Family rates the quality of the relationship between its members as very satisfactory and the concern with education and the future of the young members is still their major challenge to overcome. We can identify a dynamics based on companionship and dialogue, based on the way that couples evaluate their marriage, the decision making process in the household or how education is enforced. We hope that this knowledge proves useful and strengthens the work of psychologists and all other directly-related professional in the region